Trichoblastoma: is a clinical or dermoscopic diagnosis possible?. (21st July 2016) - Ghigliotti, G.; De Col, E.; Parodi, A.; Bombonato, C.; Argenziano, G.
Abstract: Background: Trichoblastoma is a rare benign skin tumour that must be differentiated from basal cell carcinoma for its benign course and favourable outcome. Objectives: To describe clinical and dermoscopic features of solitary primitive trichoblastoma and to compare them with trichoblastic basal cell carcinoma (tBCC). Methods: Digital dermoscopic images of 19 trichoblastoma and 19 tBCC were compared and reviewed by a dermatologist experienced in dermoscopy. Results: The most striking dermoscopic difference between trichoblastoma and tBCC was the presence of blue‐grey globules and blue‐grey ovoid nests that were found to be more frequent but not exclusive of tBCC. Arborizing vessels were found both in trichoblastoma and tBCC, with a lower frequency in the latter. Conclusion: Histology remains the gold standard to differentiate trichoblastoma from tBCC.